Penerapan Perhitungan Harga Pokok Produksi Pada CV Aulia Di Surabaya - Fitri Aulia; Sutini Sutini; Wiratna Wiratna; Diana Zuhroh; Heri Toni (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
CV. Aulia is a company engaged in the wood flooring processing industry and selling wood floors. The purpose of this study was to find out whether there is a difference between the calculation of the cost of production that has been done by the company and the calculation of the cost of production based on theory or what should be by using the Full Costing Method. This type of research is qualitative research. The research data was obtained by conducting observations, interviews, and literature studies. The results of the research show that there are differences in the difference between the calculation of the cost of production according to the company and the calculation of the cost of production based on theory or what it should be. The calculation of the cost of production used by the company so far is still very simple, namely by calculating the cost of raw materials, direct labor costs and factory overhead costs which only include indirect labor costs. The calculation of the cost of production is based on theory or should have a higher nominal value compared to the calculation of the company's cost of goods according to the company. This is because all factory overhead costs such as auxiliary costs, fuel costs, electricity costs and electricity depreciation costs are included in the calculation of the cost of production.